SOCIO-POLITICAL ASPECTS OF THE MEDIATIZATION OF POLITICS IN RUSSIA - M. M. Abazalieva; A. Y. Belokon (Современная наука и инновации, 2023)
The essence and features of the functioning of mediatized politics in the communications system of modern Russia are determined by a number of factors, which primarily include the formation of civil society, the formation of democratic foundations, and adherence to the letter of the Constitution. The purpose of the article is to identify certain semantic permutations in the communication interaction of society and government, which presuppose the presence of a pluralistic plurality of political forces and healthy competition between them, the consistent development of the system of projecting politics in the mass media. It is concluded that in modern Russia it is possible to state the tendency of the growth of the mediatization of politics in the Russian political space, which is expressed both in the transformation of the political system and the course of political processes.